SISTEM INFORMASI MANAJEMEN BANK SOAL UJIAN CALON PEGAWAI NEGERI SIPIL BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN - Tati Mardiana (LPPM Universitas Bina Sarana Informatika, 2016)
Badan Pengawasan Keuangan dan Pembangunan (BPKP) is one of the government agency aims to be better ensured implementation JFA’s development for efficiency, effectiveness and continuous. In every year, the division of Pusat Pembinaan dan Jabatan Fungsional Auditor has been charged for make CPNS’s examed. Along with the development of technology so then, the agency of BPKP have difficult experienced to make CPNS’s exams because the agency of BPKP especially division of Pusbin JFA has been charged to make CPNS’s exams whit more varied and good quality for every year in accordance with the applicable curriculum. The making system of manual are considered less effective and efficiency in processed of the data processing bank test.keyword: bank test, examination, CPNS